Study of ionic calcium in maternal and cord blood and baby′s blood at 48-h age - Neelam Deshpande; Lalit Patil; Shishir Deshpande; Sanjay Chavan (Medical Journal of Dr. D.Y. Patil University, 2014)
Background: Newborns undergo a physiological nadir in serum calcium levels by 24-48 h of age. We have compared the ionic calcium levels in serum of normal as well as high-risk pregnant mothers before delivery, in cord blood of newborns and in neonates at 48 h of age. Materials and Methods: This is a prospective study of 500 pregnant women. One hundred and twenty-two pregnant women did not receive any calcium supplementation antenatally while 378 pregnant women received calcium supplementation antenatally. Results: A statistically significant correlation was found between ionic calcium levels in mothers and in cord blood in the study population and preterm and term babies (coefficient of correlation, r = 0.83, 0.86 and 0.83, respectively). Ionic calcium in baby′s blood at 48-h age better correlated with cord blood (r = 0.67) than with maternal blood (r = 0.51). With calcium supplementation antenatally, the mean values for serum calcium of maternal blood, cord blood and baby′s blood at 48 h of age were higher than those without antenatal calcium supplementation. Conclusions: Antenatal calcium supplementation may prevent hypocalcemia in the newborn thus preventing neonatal morbidity.